2011
DOI: 10.3892/ol.2011.461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of post-operative hormone replacement therapy on life quality and prognosis in patients with ovarian malignancy

Abstract: Abstract. The present study aimed to assess the impact of post-surgical hormone replacement therapy (HRT) on life quality and prognosis in women with ovarian malignancy. HRT (Premarin, Nilestriol and medroxyprogesterone) was administered following surgery in 31 patients with ovarian cancer. A total of 44 ovarian cancer patients of similar age, clinical stage and pathological features did not receive HRT following surgery. The expression of estrogen receptor (ER)-α, ERβ and progesterone receptor (PR) in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…However, no evidence provided support for that hypothesis. A study by Li et al [25] also revealed no significant difference (p N 0.05) in survival time among patients with different ER and PR expression statuses. Hence, no concrete conclusion has been reached regarding receptor and cell responses to the clinical application of HRT.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…However, no evidence provided support for that hypothesis. A study by Li et al [25] also revealed no significant difference (p N 0.05) in survival time among patients with different ER and PR expression statuses. Hence, no concrete conclusion has been reached regarding receptor and cell responses to the clinical application of HRT.…”
Section: Discussionmentioning
confidence: 87%
“…Among those, six papers were excluded for further analysis, of which four were reviews about HRT use after an operation for gynecologic cancer, one was a descriptive study without a control group, and one was a study from duplicate data. The remaining six papers met all the eligibility criteria and thus were included in the meta-analysis [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations